(untitled) (Journal of the College of Basic Education, 2022)
Thyroid disorders known to have an impact on the fertility for both males & females. The disturbing in thyroid hormones is usually linked with the decreasing of the reproduction chances. Inhibin B also have an important role in the fertility, and it have been linked with infertility of males. This study has designed to investigate the changing in inhibin B levels in hypothyroidism females with fertility problems. The study revealed a significant difference in inhibin B levels in hypothyroidism females when compared with healthy group (p-value= 0.05), without a significant correlation to the patients age, or the body mass index. The value of 156.35 pg. /ml gives a sensitivity of 95% and specificity of 86% in the infertile women. Objective: To evaluate inhibin B in women with hypothyroidism and infertility. To investigate the body mass index for the studied groups, searching for possible correlation between body mass index and the inhibin B levels, and testing inhibin B results for sensitivity and specificity. Design: Cross-sectional, controlled study. Setting: Baghdad, Iraq. Patients: A group of infertile women with hypothyroidism (n= 50). A group of apparently healthy women (n = 40) served as controls. Interventions: venous blood samples were drawn in the cycle day 3 for patients and controls. Result(s): A significant difference in inhibin B levels has been found in hypothyroidism females when compared with healthy group (p-value= 0.05), without a significant correlation to the patients age, or the body mass index. The value of 156.35 pg. /ml gives a sensitivity of 95% and specificity of 86% in predicting the patients group. Conclusions: The infertile women with hypothyroidism have a declining level of inhibin B, and a higher body mass index than healthy women. Inhibin B levels show a high rate of sensitivity and specificity in hypothyroidism females with fertility problems.